Nonlinearity compensation of low-frequency loudspeaker response using internal model controller - Erni Yudaningtyas; Achsanul Khabib; Waru Djuriatno; Dionysius J. D. H. Santjojo; Adharul Muttaqin; Ponco Siwindarto; Zakiyah Amalia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents the nonlinearity compensation of low-frequency loudspeaker response. The loudspeaker is dedicated to measuring the response of Electret Condenser Microphone which operated in the arterial pulse region. The nonlinearity of loudspeaker has several problems which cause the nonlinearity behaviour consists of the back electromagnetic field, spring, mass of cone and inductance. Nonlinearity compensation is done using the Internal Model Controller with voltage feedback linearization. Several signal tests consist of step, impulse and sine wave signal are examined on different frequencies to validate the effectiveness of the design. The result showed that the Internal Mode Controller can achieve the high-speed response with a small error value.